Insan Akademis Berkarakter Trilogi Syarikat Islam - Nurdjidin Nurdjidin; Ahmad Hanany Nasheh (Universitas Cokroaminoto Yogyakarta, 2012)
This paper is an historical and philosophical study formulating the desired academic human character to appear on the academic community of Cokroaminoto University Yogyakarta (UCY). The community should be within guide lines of the Syarikat Islam’s trilogy which has three morals, i.e, faith, science and siyasah (strategy-charity). These characters are not only formed in the classroom, but also in the environment outside the classroom, under control of the community that has provide conditions supporting the formation of the desired three-morals. University has the main task as a provider for a conducive learning environment. This environment forms the habit of thinking independently ((habits of religious mind) as learners have made for themselves thinking as a self-obligation; of religious thinking, critical thinking, academic thinking, as well as strategic and creative thinking.